ICTs for Education in Africa - Souter, David; Adam, Lishan; Butcher, Neil; Sibthorpe, Claire; Tusubira, Tusu (World Bank, Washington, DC, 2014)
The future development of Africa and its participation in the knowledge society will be greatly influenced by how Africa manages to deliver quality education to its citizens. Education forms the basis for developing innovation, science, and technology, in order to harness resources, industrialize, and participate in the global knowledge economy and for Africa to take its rightful place in the global community. While information and communication technology (ICT) has been used in many parts of the world to improve the quality and increase access to education, most African countries still face the challenge that increased expenditure on education is not necessarily achieving the expected benefits. This report examines the potential for the use of ICT to support improvement and transformation of the education sector in Africa, including brief case studies of South Africa, Uganda, and Senegal. It identifies specific opportunities and challenges, and recommends areas of intervention for governments, development partners, and other stakeholders. It looks in particular at the following five areas: teacher professional development; digital learning resources; affordable technologies; education management information systems (EMIS); and national research and education networks (NRENs).